RANCANG BANGUN MODUL PRAKTIKUM SISTEM EMBEDDED BERBASIS RASPBERRY PI (MODUL 2: PENERAPAN SISTEM SEDERHANA) - Pawesi Siantika, I Putu; Rahardjo, Pratolo; Raka Agung, I Gusti Agung Putu (Jurnal SPEKTRUM, 2021)
Embedded systems play a very important role in various fields so that several universities, especially Udayana University in the Electrical Engineering Study Program, Faculty of Engineering have included embedded systems + lab courses. However, the availability of supporting facilities for activities in the lab is not yet available as it should be. Based on this, in this research, a practicum module for an embedded system based on Raspberry Pi will be designed and made (Module 2: implementation of a simple system). This practicum module has three experiments, namely a lamp control system and a 5 V DC motor equipped with an LDR sensor (experiment 1); monitoring the water level using the HC-SR04 sensor module and the height data is displayed on a 16 x 2 LCD (experiment 2); Human movement detection uses the HC-SR501 sensor module with output in the form of audio that is channeled to the speaker, the image display by the 0.96 inch OLED module, and the rotation of the LDR servo shaft (experiment 3). The results obtained in the three experiments are that all systems work successfully with the following conditions: The load on the relay turns on when the LDR sensor condition is covered with black cloth, the load on the relay goes out when the LDR sensor condition is left unobstructed and the LDR sensor is illuminated by an LED flashlight. The LED indicator lights up according to the condition of the water level reading by the HC-SR04 sensor module. The HC-SR501 sensor module successfully detects the movement of objects in the form of humans at a distance of 1 m, 1.5 m, and 3 m.